Ethical Reflections on Nurse–Patient Communication in Obstetric Clinical Practice: An Expanded Academic Revision - Nian Wang (Journal of Psychology & Education, 2026)
Obstetric care involves the simultaneous safeguarding of maternal and neonatal well-being and is characterized by high risk, high emotional intensity, and persistent communication demands. In this context, nurse–patient communication is not merely a technical adjunct to nursing practice but a core ethical activity that shapes care quality, patient safety, emotional well-being, treatment adherence, and the overall climate of clinical trust. Pregnant and postpartum women constitute a distinctive patient group whose physical condition, psychological status, and decision-making needs shift dynamically across the antenatal, intrapartum, and postpartum continuum. Consequently, communication in obstetric settings requires a higher level of professional sensitivity, ethical discipline, and person-centered responsiveness than is often assumed in general inpatient care. Drawing on the four foundational principles of biomedical ethics—respect for autonomy, beneficence, nonmaleficence, and justice—this revised paper provides a more theoretically grounded and analytically rigorous examination of common communication problems in obstetric nursing. It argues that persistent weaknesses in informed communication, privacy protection, empathic engagement, language regulation, and equitable service delivery are not isolated behavioral lapses but manifestations of deeper structural tensions between efficiency-oriented care routines and the ethical demands of patient-centered maternity care. The paper further proposes a full-cycle ethical communication framework for obstetric practice, integrating graded informed consent, privacy-sensitive communication protocols, empathy-based psychological support, standardized low-harm language strategies, stratified yet equitable communication planning, and department-level quality governance. By strengthening conceptual depth and practical applicability, this article aims to contribute to the construction of a more humane, ethically coherent, and clinically effective model of obstetric nursing communication.